Enhancement of field electron emission in topological insulator Bi2Se3 by Ni doping - Mazumder, K.; Sharma, A.; Kumar, Y.; Bankar, P.; More, M. A.; Devan, R.; Shirage, P. M. (Physical Chemistry Chemical Physics, 2018)
Nanostructures of bismuth selenide (Bi2Se3), a 3D topological insulator material, and nickel (Ni) doped Bi2Se3 samples were prepared by a hydrothermal method to explore the field emission properties. An enrichment in the field electron emission (FE) properties in terms of the threshold and turn-on field values of Bi2Se3 and Ni doped Bi2Se3 nanostructures was measured at a base pressure of ∼1 × 10−8 mbar. Using the background of the Fowler–Nordheim (FN) theory a field enhancement factor (β) of 5.7 × 103 and a threshold field value of 2.5 V μm−1 for 7.5% Ni doped Bi2Se3 were determined by investigating the J–E plot of the FE data. The value of β is three times higher than that of pure Bi2Se3 confirming the superior FE properties. The emission current was found to be very stable with the property of long standing durability as a negligible amount of variation was observed when measured at a constant value of 5 mA for 3 hours. The experimental results signify many opportunities for potential applications of Ni doped Bi2Se3 as a source of electrons in scanning as well as transmission electron microscopy, flat panel displays and as an X-ray generator, etc.

VSe2-reduced graphene oxide as efficient cathode material for field emission - Ratha, S. (Journal of Physics and Chemistry of Solids, 2019)
Field emission properties of pristine VSe2 and its hybrid with reduced graphene oxide (RGO) have been investigated in detail. Promising field emission performance were noted with lower values of turn-on and threshold fields of ∼1.3 V μm−1 and 2.12 V μm−1 respectively for the VSe2/RGO hybrid which is much more superior than that of pristine VSe2 emitter and other 2D materials. Density Functional Theory (DFT) simulations have also been performed to qualitatively support our experimental observations through demonstration of Density of States and computation of work function for pristine VSe2 and hybrid VSe2/RGO. The lowering of work function and appearance of additional states near Fermi level from carbon p orbital of RGO is responsible for superior field emission characteristics in hybrid VSe2/RGO compared to pristine VSe2 which supports our experimental observations. Our experimental data and theoretical insight from electronic structure simulations strongly infer that the synthesized hybrid VSe2/RGO has the potential to be tailored as efficient and high performance cathode material in field emission based devices.
Keywords: cathode material; Chalcogenide; Density functional theory; field emission; Vanadium diselenide; Work function